Orthostatic Intolerance in Adults Reporting Long COVID Symptoms Was Not Associated With Postural Orthostatic Tachycardia Syndrome - Monaghan, Ann; Jennings, Glenn; Xue, Feng; Byrne, Lisa; Duggan, Eoin; Romero-Ortuno, Roman (Frontiers in Physiology, 2022)
In this observational cross-sectional study, we investigated predictors of orthostatic intolerance (OI) in adults reporting long COVID symptoms. Participants underwent a 3-minute active stand (AS) with Finapres® NOVA, followed by a 10-minute unmedicated 70-degree head-up tilt test. 85 participants were included (mean age 46 years, range 25-78; 74% women), of which 56 (66%) reported OI during AS (OIAS). OIAS seemed associated with female sex, more fatigue and depressive symptoms, and greater inability to perform activities of daily living (ADL), as well as a higher heart rate (HR) at the lowest systolic blood pressure (SBP) point before the 1st minute post-stand (mean HRnadir: 88 vs 75 bpm, P=0.004). In a regression model also including age, sex, fatigue, depression, ADL inability, and peak HR after the nadir SBP, HRnadir was the only OIAS predictor (OR=1.09, 95% CI: 1.01-1.18, P=0.027). 22 (26%) participants had initial (iOH) and 5 (6%) classical (cOHAS) orthostatic hypotension, but neither correlated with OIAS. 71 participants proceeded to tilt, of which 28 (39%) had OI during tilt (OItilt). Of the 53 who had a 10-minute tilt, 7 (13%) had HR increase >30 bpm without cOHtilt (2 to HR >120 bpm), but 6 did not report OItilt. In conclusion, OIAS was associated with a higher initial HR on AS, which after 1 minute equalized with the non-OIAS group. Despite these initial orthostatic HR differences, POTS was infrequent (2%). ClinicalTrials.gov Identifier: NCT05027724 (retrospectively registered on August 30, 2021).